1993
DOI: 10.1109/55.215159
|View full text |Cite
|
Sign up to set email alerts
|

Microwave performance of a self-aligned GaInP/GaAs heterojunction bipolar transistor

Abstract: Microwave performance of a self-aligned GaInP/ GaAs heterojunction bipolar transistor (HBT) is presented. At an operating current density of 2.08 X lo4 A/cmZ, the measured cutoff frequency is 50 GHz, and the maximum oscillation frequency extrapolated from measured unilateral gain and the maximum available gain are 116 and 81 GHz, respectively, all using 20-dB/decade slopes. To the author's knowledge, these represent the highest reported values of HBT's based on the GaInP/GaAs material system. These results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Also, InGaP can be fabricated with a low concentration of deep-level defects, and each of the InGaP and GaAs layers can be etched selectively with respect to each other with natural etch stops at the heterointerfaces. Excellent results have been obtained for high-power lasers, 4 heterojunction bipolar transistors, 5 and solar cell device systems, 6,7 especially for use on satellites in low earth orbits where exposure to radiation is high. 8,9 Recently, persistent photoconductivity ͑PPC͒ has been observed in GaInP/GaAs heterostructures, and it is suggested that the PPC effect is due to the existence of DX centers in GaInP layers similar to that of AlGaAs/GaAs heterostructures.…”
mentioning
confidence: 85%
“…Also, InGaP can be fabricated with a low concentration of deep-level defects, and each of the InGaP and GaAs layers can be etched selectively with respect to each other with natural etch stops at the heterointerfaces. Excellent results have been obtained for high-power lasers, 4 heterojunction bipolar transistors, 5 and solar cell device systems, 6,7 especially for use on satellites in low earth orbits where exposure to radiation is high. 8,9 Recently, persistent photoconductivity ͑PPC͒ has been observed in GaInP/GaAs heterostructures, and it is suggested that the PPC effect is due to the existence of DX centers in GaInP layers similar to that of AlGaAs/GaAs heterostructures.…”
mentioning
confidence: 85%
“…Excellent results have been, in particular, obtained for high power laser diodes 1 and heterojunction bipolar transistors. 2,3 For these specific applications, GaInP is favorably replacing AlGaAs. However, the material science related to the GaInP/ GaAs heterojunction is far from being so well understood as for the case of AlGaAs/GaAs.…”
mentioning
confidence: 99%
“…Lattice-matched In 0.485 Ga 0.515 P/GaAs hetero-structures are becoming major III-V semiconductor systems, because compared with AlGaAs/GaAs systems, they have lower reactivity with oxygen, higher number of reduced DX centers [1], and lower interfacial recombination rates [2]. InGaP/GaAs hetero-structures are thus attractive alternatives to AlGaAs/GaAs systems for applications in hetero-structure field-effect transistors (HFETs) [3,4], hetero-junction bipolar transistors (HBTs) [5,6], high power lasers [7][8][9], and solar energy conversion devices [10][11][12].…”
Section: Introductionmentioning
confidence: 99%